GROWTH AND NUTRIENT ACCUMULATION AND EXPORT IN A SHORT-DAY ONION - Moraes, Carolina Cinto de (2018)
New hybrid onions that are more productive are currently being cultivated. Information on growth and nutrient accumulation must thus be updated to assist in the refinement of existing recommendations, enabling the better exploitation of the productive potential of these new genotypes. We determined the growth of plants and the accumulation and export of nutrients of the short-day onion ‘Soberana’ established by direct seeding. The experimental design was a randomized block with four replicates and the treatments were evaluation times. Leaf number, tissue dry weight, nutrient accumulation, and the maximum daily rate of accumulation were evaluated throughout the growing cycle. The order of nutrient accumulation was (g plant-1) K (0.72) > Ca (0.38) > N (0.32) > S (0.14) > P (0.08) > Mg (0.06) and (mg plant-1) Fe (2.26) > Mn (1.43) > Cu (0.93) > Zn (0.91) > B (0.85). Macronutrient demand was highest between 61 and 148 days after sowing (DAS), and micronutrient demand was highest between 70 and 148 DAS.